Development and validation of a QTrap method for sensitive quantification of sphingosine 1‐phosphate. (5th November 2020) - Müller, Tina; Gräler, Markus H.
Abstract: Sphingosine 1‐phosphate (S1P) is a bioactive phospholipid and ligand for five G protein‐coupled cell‐surface receptors designated S1PR1–5. The determination of low levels of S1P remains a challenge and usually requires sophisticated analytical instrumentation and methodology. This report describes a technique using the linear ion trap mode of a basic QTrap triple‐quadrupole mass spectrometer. S1P was extracted from acidified biological samples using a modified Folch extraction procedure. After the addition of C17‐sphingosine as an internal standard, a step gradient LC method was used to separate the analytes on a reversed‐phase C18 MultoHigh analytical column. After the internal standard C17‐sphingosine was detected by multiple reaction monitoring (MRM), the detection mode was switched to enhanced product ion (EPI) mode for the detection of S1P. The mode was switched back to MRM again for the detection of other analytes. Using this QTrap method, we reached a limit of detection of 1 nM and a limit of quantification of 3 nM for S1P, which was up to 30 times more sensitive than the MRM mode with the same instrument. Intra‐day precision ranged between −3.8 and 6.3%, and inter‐day precision was between −13.8 and 3.3%, depending on the spiked S1P concentration.